Effect of industrial grade chitosan on the ripening period of newly harvested mango (Mangifera indica Linn. CV. carabao) - Tayona, John Earl Peregrino (1997.)
Newly harvested carabao mangoes were treated with industrial grade chitosan, a polysaccharide derived from shellfish wastes, to evaluate its effect on the fruit's ripening period.
Thesis (Graduate, Bachelor of Science in Food Technology) School of Technology, University of the Philippines in the Visayas.
Keywords: Chitosan; Mango